Radioassay facilities at the STFC Boulby Underground Laboratory - Scovell, Paul R.; Thiesse, Matthew; Ahmed Maouloud, Sid; Ghag, Chamkaur; Dobson, James (Frontiers in Physics, 2023)
For future low-background particle physics experiments, it will be essential to assay candidate detector materials using an array of assay techniques. To minimise the risk of sample contamination whilst moving between assay techniques, it is also sensible to minimise the distance between assay stations, particularly for non-destructive techniques where the sample may end up being installed into an experiment. The Boulby Underground Screening (BUGS) Facility comprises an array of germanium detectors, two XIA UltraLo-1800 surface-alpha counters, two radon emanation detectors and an Agilent ICP-MS system. This article describes each of these systems.